A randomized, double‐blind, placebo‐ and active‐controlled, half‐head study to evaluate the effects of platelet‐rich plasma on alopecia areata. (30th August 2013) - Trink, A.; Sorbellini, E.; Bezzola, P.; Rodella, L.; Rezzani, R.; Ramot, Y.; Rinaldi, F.
Summary: Background: Alopecia areata (AA) is a common autoimmune condition, causing inflammation‐induced hair loss. This disease has very limited treatment possibilities, and no treatment is either curative or preventive. Platelet‐rich plasma (PRP) has emerged as a new treatment modality in dermatology, and preliminary evidence has suggested that it might have a beneficial role in hair growth. Objectives: To evaluate the efficacy and safety of PRP for the treatment of AA in a randomized, double‐blind, placebo‐ and active‐controlled, half‐head, parallel‐group study. Methods: Forty‐five patients with AA were randomized to receive intralesional injections of PRP, triamcinolone acetonide (TrA) or placebo on one half of their scalp. The other half was not treated. Three treatments were given for each patient, with intervals of 1 month. The endpoints were hair regrowth, hair dystrophy as measured by dermoscopy, burning or itching sensation, and cell proliferation as measured by Ki‐67 evaluation. Patients were followed for 1 year. Results: PRP was found to increase hair regrowth significantly and to decrease hair dystrophy and burning or itching sensation compared with TrA or placebo. Ki‐67 levels, which served as markers for cell proliferation, were significantly higher with PRP. No side‐effects were noted during treatment. Conclusions: This pilot study, which is the first to investigate the effects of PRP on AA, suggests that PRP may serve as a safe and effective treatment option in AA, and calls for more extensive controlled studies with this method. Abstract : What's already known about this topic? Platelet‐rich plasma (PRP) has emerged as a new treatment modality in dermatology, and preliminary evidence has suggested that it might have a beneficial role in hair growth. No study has ever evaluated the effect of PRP on hair growth in patients with alopecia areata (AA). What does this study add? PRP was found to increase hair regrowth compared with triamcinolone acetonide or placebo, and Ki‐67 levels were significantly higher. PRP also decreased the percentage of dystrophic hairs and burning or itching sensation. This study, which is the first to investigate the effects of PRP on AA, suggests that PRP may serve as a safe and effective treatment option in AA.